The art of the fall - Côté, Véronique (QC Fiction, 2020)
A story about love, art, and the 2008 financial crisis. Towards the end of the 18th century, twenty-four traders would meet under a tree to buy and sell shares. The tree was located at 68 Wall Street, so called because of a wall that used to mark the northern limits of the colony of New Amsterdam, on the Island of Manhattan. On May 17, 1792, the twenty-four brokers signed, beneath the tree, the Buttonwood Agreement. This marked the foundation of the New York Stock Exchange, and the birth of Wall Street. Today, the tree on Wall Street has long since fallen, and the twenty-four traders' transactions have become complex to the point of being almost intangible and immaterial. Finance has become an abstraction; it pervades every sphere of our lives, including contemporary art. Especially contemporary art. This love story, based on documentary research, follows a struggling artist and an opportunistic hedge fund manager. As Lehman Brothers falls and two worlds collide, we explore the darkest corners of the contemporary art scene, the global economy, and two broken hearts.